EFEKTIVITAS PEMBELAJARAN PAK DENGAN METODE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD KANISIUS KURMOSARI SEMARANG - Linda Elvira Ndruru; Sugiyana Sugiyana; FR. Wuriningsih (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
The teaching and learning process is an ongoing interaction between teachers and students to acquire knowledge in accordance with learning objectives. Measuring the success of the teaching and learning process can be seen from the learning outcomes achieved by students. The purpose of this study was to determine whether the snowball throwing method was more effective in influencing student responsibility than the conventional method, the effect of the responsibility of students taught by the snowball throwing method on student achievement, and the effectiveness of using the snowball throwing method in improving student achievement. This type of research is quantitative with a True Experimental research design using a Pretest-Posttest Control Group Design. Data was collected by means of tests, observations, and documentation. After the data was collected, data analysis was carried out so that the average experimental class student responsibility was 3,25 higher than the control class average responsibility of 1,9 so that the snowball throwing method in the experimental class was more effective in influencing student responsibility. Student responsibility is very influential on student achievement of 83,0%. The use of the snowball throwing method was more effective in improving the learning achievement of fifth-graders at SD Kanisius Kurmosari Semarang in Catholic Religious Education subjects by 76,8497 or 76,8%. So, the use of the snowball throwing method is more effective in improving student learning outcomes.